2021
DOI: 10.1177/17531934211029511
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 3-D corrective osteotomies for paediatric malunited both-bone forearm fractures

Abstract: Closed treatment of paediatric diaphyseal forearm fractures carries the risk of re-displacement, which can lead to symptomatic malunions. This is because growth will not correct angulation deformity as it does in metaphyseal fractures. The purpose of this prospective cohort study was to evaluate the outcomes after 3-D-planned corrective osteotomy with patient-specific surgical guides for paediatric malunited forearm fractures causing impaired pro-supination. Our primary outcome measure was the gain in pro-supi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Several studies describe 3D-planned corrective limb osteotomies and show their technique to be feasible, leading to good functional outcomes [6][7][8][9][10][11][12][13][14]. Yet, even though the surgery is planned using state-of-the-art 3D software, postoperative evaluation is usually still performed in 2D on plain radiographs since postoperative CTs are not routinely made.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies describe 3D-planned corrective limb osteotomies and show their technique to be feasible, leading to good functional outcomes [6][7][8][9][10][11][12][13][14]. Yet, even though the surgery is planned using state-of-the-art 3D software, postoperative evaluation is usually still performed in 2D on plain radiographs since postoperative CTs are not routinely made.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, even though the surgery is planned using state-of-the-art 3D software, postoperative evaluation is usually still performed in 2D on plain radiographs since postoperative CTs are not routinely made. Therefore, the majority of these studies evaluated their achieved accuracy based on postoperative radiographs, thereby only providing the accuracy in two dimensions: the anteroposterior and lateral direction [6][7][8][9]11]. Since the performed correction was planned in three dimensions, it is essential to assess the postoperative result in three dimensions as well to provide the accuracy of the performed correction and to gain insight into the cause of deviation in relation to suboptimal clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corrective osteotomies are conventionally planned and assessed manually on (biplanar) twodimensional (2D) radiographs 125 . However, recent studies have shown that computer-assisted preoperative planning based on three-dimensional (3D) Computed Tomography (CT) scans significantly improved both functional and radiographic outcome [125][126][127][128] .…”
Section: Introductionmentioning
confidence: 99%